Autologous Fat Transfer for Facial Augmentation: Surgery and Regeneration. Issue 3 (May 2019) - Clauser, Luigi; Zavan, Barbara; Galiè, Manlio; Di Vittorio, Leonardo; Gardin, Chiara; Bianchi, Andrea Edoardo
Abstract : Abstract: Autologous fat transfer (AFT) is a well-established and safe surgical technique in which autologous fat tissue is injected at a defective site directly after its harvesting and centrifugation. Initially used as an excellent filler for facial enhancement and rejuvenation, AFT has evolved over the years into more complex reconstructive procedures. Autologous fat transfer is now additionally used for correcting and restoring cranial and maxillofacial volume defects resulting from traumas, tumors, or congenital disorders. Apart from being a natural filler, human adipose tissue represents a rich source of mesenchymal stem cells, called adipose-derived stem cells, that exhibit multilineage differentiation potential and secrete several angiogenic and antiapoptotic factors. In this work, the authors will discuss different aspects influencing the final outcome of AFT, on the basis of the major clinical outcomes obtained using this surgical procedure. Starting from preoperative evaluation and planning, donor–recipient sites, and type of anesthesia and infiltration, the discussion will continue by analyzing the methods of adipose tissue harvesting, purification, and processing. Finally, an overview of the type of placement, clinical application, postoperative care, possible complications, fat graft take, longevity, volume maintenance, and future perspectives will be provided.